Factors Influencing Participation in Peer-To-Peer Accommodation – A Systematic & Bibliometric Review - Kanwalpreet Kaur, Sheetal Kapoor (Journal of Informatics Education and Research, 2024)
Accommodation options offered under sharing economy model, also known as peer-to-peer (P2P) accommodation, have seen a burgeoning demand in the tourism sector over the last decade and offered tough competition to the traditional hotel industry. In the light of increasing curiosity among academia and practitioners, we explore the extant literature pertaining to factors affecting visitor’s intention to participate in P2P accommodation during travel. This study examines 127 research articles identified from two databases (Scopus and Web of Science) over the period of 2000-2023 and screened using PRISMA methodology. Bibliometric analysis combined with systematic literature review (SLR) was conducted employing Theory-Context-Characteristics-Methodology (TCCM) framework with an aim to uncover present status of scholarly research, existing gaps and prospective areas of inquiry. Trust and sustainability has emerged as key themes with growing popularity whereas Airbnb has appeared as the most widely studied platform. Future research directions for P2P accommodation are also discussed.